Utilization Analysis of Cloud Computing on SMEs : Systematic Review - Lila Setiyani; Luis Makluf; Yahya Suherman (Association for Scientific Computing Electrical and Engineering, 2020)
Business Process Management Strategy of a company is not separated from the use of digital technology. The Implementation of digital technology in a company can be supported using cloud computing service, which contributes to the access, data security and other benefits that can improve the productivity and performance of the company. SMEs is a type of business that is being encouraged by the government to improve the nation's economy. SMEs have the potential to increase productivity through cloud computing services. Based on the type of cloud computing, it is divided into three types namely IaaS (Infrastructure As a Service), PaaS (Platform As a Service) and SaaS (Software As a Service) which can be utilized based on the needs of each business person. This systematic review aims to analyze the types of cloud computing that support SMEs business processes. The method used in compiling this systematic review is by using the PRISMA Framework. This systematic review reviews twelve articles. The result of this systematic review is a list of cloud computing support for SMEs that can be implemented by other SMEs in increasing productivity and performance.